Characterizing Nigeria’s cassava seed system and the use of planting material in three farming communities - Pircher, T.; Obisesan, D.; Nitturkar, H.; Asumugha, G.N.; Ewuziem, J.; Anyaegbunam, H.; Azaino, E.; Akinmosin, B.; Ioryina, A.; Walsh, S.; Almekinders, Conny J.M. (International Potato Center, 2019)
To archive a larger impact of seed interventions, we need to understand root, tuber and banana seed systems better. In the context of the intervention “Building an Economically Sustainable, Integrated Seed System for Cassava in Nigeria” (BASICS), there was a need to better understand the seed-sourcing behavior of cassava farmers and identify entry points for decentralized stem multipliers (DSMs). To this end a multi-stakeholder workshop provided insights into the wider landscape of Nigeria’s cassava seed system. In an explorative study we collected qualitative data via focus group discussions and complemented them with quantitative data from a survey of 90 cassava farmers in three study sites with different agro-ecological conditions. Our findings show that the cassava seed system is largely informal with vibrant stem trade within and between communities. Farmers in all study sites maintain a mix of varieties with multiple traits that is adapted to agro-ecological conditions and farmers’ preferences for use of roots. They value short maturity for early harvest, long storage of roots in the soil, bitterness as a protection against rodents, and high starch content for preparation of fufu. Although farmers in Nigeria’s South South region used only local landraces, farmers in other study sites dynamically combine those with new germplasm from the formal system. Because of a longer dry season, not all farmers are able to cover their need of planting material from their own fields alone. Despite using technologies for storage of cassava stems, there is still a demand for stems from relatives, friends, and neighbors; local traders and seed markets; and agricultural development programs. Differentiation of farmer categories by the size of their cassava fields showed no explainable pattern of different seed-sourcing behavior. Across the study population, the shortage of planting material and farmers’ interest in trying out new varieties were identified as entry points for the DSMs of the BASICS project. Further research on seed-sourcing dynamics, however, is needed to create a clear profile of stem buyers. We emphasize the importance of understanding the dynamics and the involvement of various actors in informal seed exchange to harmonize the work of DSMs in a seed system.